Morphological Changes In Gastrointestinal Tract Of Post- Hatch Broiler Chicken - Mandal, A.K.; Das, R.K.; Mishra, U.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
The present study was conducted on "Vencob" broiler chickens reared during post-hatch period from day 1 up to day 48. Birds were sacrificed at weekly interval and carefully dissected to examine thoroughly different segments of gastrointestinal tract from esophagus to cloaca. The gross morphometrical parameters ( length, weight ) for each and every gut segment were recorded. The relative length and relative weight were calculated. All the morphometrical parameters showed a gradual increase from day 1 till the end of the experimental period. However, duodenal and jejunal length increased more rapidly up to day 8 post- hatch, followed by a gradual increase thereafter. Except the duodenum (till 8th day), all other segments revealed a declining trend in relative length and relative weight. Rate of increase in these biometrical values was comparatively less during the later part of experimental period. In general, with age all the gut segments increased in length and weight parallel to the body growth of the birds.